EVALUATION OF TOPICAL KETOCONAZOLE EFFECTS ON THE REGENERATION OF CORNEAL EPITHELIUM - EXPERIMENTAL-STUDY IN RABBITS - Jorge, Edson Nacib [UNESP] (1995)
UNIV ESTADUAL PAULISTA,DEPT OPHTHALMOL,SAO PAULO,BRAZIL